The Role of Islamic Banking in Encouraging Financial Inclusion in Indonesia - Wahyuni; Yesi Safitri; Wahyuni Sirait; Ismail (JIM: Jurnal Ilmiah Mahasiswa, 2026)
Islamic banking has a strategic role in expanding financial inclusion in Indonesia through the application of the principles of justice, benefit, and sustainability. This research uses a qualitative method with literature studies from various current journals that discuss financial digitalization, sharia literacy, and strengthening the halal economic ecosystem. The results of the study show that Islamic banking contributes to increasing public access to financial services through micro products, digital innovation, and Islamic financial literacy programs. Synergy between regulators, industry, and social institutions is key in accelerating fair and sustainable Islamic financial inclusion. However, challenges such as low Islamic financial literacy and limited service networks still need to be overcome so that the role of Islamic banking is more optimal in supporting national economic development.